2004
DOI: 10.1086/381075
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in the Colors of Lyman Break Galaxies from z ~ 4 to z ~ 3

Abstract: The integrated colors of distant galaxies provide a means for interpreting the properties of their stellar content. Here we use rest-frame UV-to-optical colors to constrain the spectral energy distributions and stellar populations of color-selected, B-dropout galaxies at in the Great Observatories Origins Deep Survey (GOODS). We z ∼ 4 combine the Advanced Camera for Surveys data with ground-based near-infrared images, which extend the coverage of galaxies at to the rest-frame B band. We observe a color-magnitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 20 publications
7
66
1
Order By: Relevance
“…These studies suggest a general trend of decreasing dust content of galaxies to earlier cosmic times, to lower luminosities, and to lower masses (though the observed trends may be enhanced by changes in the ages or metallicities). Similar trends are found as a function of the rest-frame optical luminosity of galaxies, as seen with Spitzer/IRAC (Oesch et al 2013b; see also Papovich et al 2004) and also in large cosmological hydrodynamical simulations (e.g., Finlator et al 2011: see Bouwens et al 2012aFinkelstein et al 2012).…”
Section: Introductionsupporting
confidence: 74%
“…These studies suggest a general trend of decreasing dust content of galaxies to earlier cosmic times, to lower luminosities, and to lower masses (though the observed trends may be enhanced by changes in the ages or metallicities). Similar trends are found as a function of the rest-frame optical luminosity of galaxies, as seen with Spitzer/IRAC (Oesch et al 2013b; see also Papovich et al 2004) and also in large cosmological hydrodynamical simulations (e.g., Finlator et al 2011: see Bouwens et al 2012aFinkelstein et al 2012).…”
Section: Introductionsupporting
confidence: 74%
“…The interpretation of this relation depends on which color is used. If the color is between the rest-frame UV and the rest-frame optical (e.g., Papovich et al 2004) and spans the 4000 Å/Balmer break, then it is strongly dependent on the stellar population age, while if the color is blue-ward of the 4000 Å break (e.g., Finkelstein et al 2012) then it is more sensitive to the dust extinction than age. Here we use rest-frame UV colors (i.e., UV spectral slope, β) to infer the color-magnitude relation for SFGs at 2 < z < 2.5.…”
Section: β Versus M 1500mentioning
confidence: 99%
“…While we cannot solve these degeneracies on an object-by-object basis without deep multi-wavelength photometry, we can use recent results from literature to explain the general trends observed. Deep studies of dropouts covering a wide range in both redshift and UV luminosity have now clearly demonstrated that starforming galaxies become bluer in the UV continuum with increasing redshift and with decreasing luminosity (Papovich et al 2004;Stanway et al 2005;Hathi et al 2008;Bouwens et al 2009), in some contrast with earlier results that indicated no clear correlation between the slope of the UV continuum and UV luminosity (e.g., Meurer et al 1999;Adelberger & Steidel 2000;Ouchi et al 2004). As shown by Bouwens et al (2009), these results can be fully explained by the relatively limited range in redshift and/or UV luminosity probed by earlier surveys.…”
Section: Interpreting the Relation Between M * And The Z-[36] Colormentioning
confidence: 99%